Work environment and work culture on performance through organizational citizenship behavior - Sugiarto, Awan; Santoso, Budi; Suharsono, Riyanto Setiawan; Nursaid, Nursaid (Pusat P2M Politeknik Negeri Batam, 2026)
This study aims to analyze the effect of work environment and work culture on performance with Organizational Citizenship Behavior (OCB) as an intervening variable. The research method used is a quantitative survey. Data were collected via questionnaires distributed by staff in Kaliwates District and analyzed using WarpPLS. The results showed that the work environment and work culture significantly affect employee performance. The work environment and culture also significantly affect OCB. Furthermore, OCB significantly mediates the effect of the work environment and work culture on employee performance. This study recommends that government organizations focus on building a conducive work environment and a positive work culture to improve OCB and employee performance, as a reference for HR development and improving public services.